Impact of critical care environment on burnout, perceived quality of care and safety attitude of the nursing team - Edinêis de Brito Guirardello
ABSTRACT Objective: assess the perception of the nursing team about the environment of practice in critical care services and its relation with the safety attitude, perceived quality of care and burnout level. Method: cross-sectional study involving 114 nursing professionals from the intensive care unit of a teaching hospital. The following instruments were used: Nursing Work Index-Revised, Maslach Burnout Inventory and the Safety Attitude Questionnaire. Results: the professionals who perceived greater autonomy, good relationships with the medical team and better control over the work environment presented lower levels of burnout, assessed the quality of care as good and reported a positive perception on the safety attitude for the domain job satisfaction. Conclusion: the findings evidenced that environments favorable to these professionals' practice result in lower levels of burnout, a better perceived quality of care and attitudes favorable to patient safety.